Safety climate responses and the perceived risk of accidents in the construction industry - Meliá, J.; Mearns, K.; Silva, S.A.; Lima, M. L. (Safety Science, 2008)
The usefulness of safety climate as a diagnostic tool ought to reside in its ability to identify detailed and precise difficulties that can be considered critical to improving safety. This feature depends on the theoretical analysis of the agents and issues that should be included in safety climate statements. Safety climate can be analysed from the point of view of the agent that performs the safety response in question, by identifying four main safety agents (organization, supervisors, co-workers and worker) and five safety climate variables: the Organizational Safety Response (OSR), the Supervisors’ Safety Response (SSR), the Co-Workers’ Safety Response (CSR), the Worker Safety Response (WSR), and the perceived risk of accidents. The aim of this paper is to analyse the psychosocial chain of safety influences among the safety responses and the perceived probability of accidents. Two general samples were obtained in England (N = 869) and Spain (N = 113) and two construction samples in China (N = 99) and Spain (N = 374). In both the general and construction samples, OSR and SSR are strongly related, as are CSR and WSR. Construction samples present some characteristic differences, especially in the link between the safety responses of the managerial and worker levels and the prediction of perceived risk.